ANTECEDENTS FROM SWITCHING INTENTION THE CUSTOMER’S BANK - Sofia Puspitaningtyas (Universitas Trisakti, 2014)
Now day’s competition at Indonesia banking industry getting strong and difficult. Every bank provides the similar event on same product or service with another bank and continuously tries to improve their quality of service. Not only provides the same or similar products and services, they also try to attract customers with thousand of promises. Refer to that condition, it is easier for the customers to switch from one bank to another bank.This study is designed to identify the factors that influence the customer to switch the bank. The design of this research applies quantitative research by testing the theories through measurement of research variables with numbers and analyzing data with statistical procedures. 170 respondents participated in this study but 154 questioners acceptable to used in this study. The study consisted of seven variables: customer expertise, word of mouth, service quality, switching cost, price, commitment and intention of switching banks. Data analysis applied measuring method on the calculation of reliability, validity, and multiple regression analysis performed using SPSS 15.0 module.The result of the research indicated that word mouth and price have positive impact to drive customer switching to another service provider/bank. Service quality has the negative effect to customer switching intention. In the other hand customer expertise, switching cost and bank commitment have no effect on customer switching intention.The research implies the bank’s founding management once they make strategies to retain their customer or to minimize customer switching intention. Suggest exploring other antecedents of switching intention on future study providers such as reputation, the attractiveness of another alternative, the effectiveness of advertising and anger accident.